High Density Lipoproteins From Biological Understanding to Clinical Exploitation - von Eckardstein, Arnold; Kardassis, Dimitris (Handbook of Experimental Pharmacology, 2015)
Pharmacology/Toxicology; Molecular Medicine; Human Physiology; Immunology; Cell Biology